2015
DOI: 10.1039/c5ra08416d
|View full text |Cite
|
Sign up to set email alerts
|

Controllable in situ synthesis of BiOBrxI1−x solid solution on reduced graphene oxide with enhanced visible light photocatalytic performance

Abstract: Novel composite photocatalysts, BiOBr x I 1Àx -rGO, were facilely prepared by in situ controllable deposition of BiOBr x I 1Àx solid solutions onto the surface of graphene oxide which was then reduced at mild conditions. The high-resolution transmission electron microscopy results revealed an intimate interface between BiOBr x I 1Àx and rGO in the composites. The UV-vis diffuse reflectance spectra showed that BiOBr x I 1Àx -rGO composites had intense optical absorption in the visible light region. These excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 52 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…where a represents absorption coefficient, h represents Planck constant, n represents light frequency, A represents a constant, and E g represents band gap. 45 By extrapolating to the X axis (Fig. 11b), the band gap energies of BiOI and P-BiOI both were calculated to be 1.77 eV, which implies that phosphorus doping does not affect the value of the band gap.…”
Section: Optical Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…where a represents absorption coefficient, h represents Planck constant, n represents light frequency, A represents a constant, and E g represents band gap. 45 By extrapolating to the X axis (Fig. 11b), the band gap energies of BiOI and P-BiOI both were calculated to be 1.77 eV, which implies that phosphorus doping does not affect the value of the band gap.…”
Section: Optical Propertiesmentioning
confidence: 94%
“…The degradation of organic dyes may involve one or more of the active groups such as cOH, h + and cO 2 À . 18,45,52 To investigate the function of these active groups, different scavengers are added to the photocatalytic reaction system, respectively. The ethylenediaminetetraacetic acid disodium (EDTA-2Na) is used as the scavenger for h + , and the benzoquinone (BQ) is used as the scavenger for cO 2 À and the iso-propyl alcohol (IPA) is used as the scavenger for cOH (Fig.…”
Section: Possible Photocatalytic Mechanismmentioning
confidence: 99%
“…Recently, graphene exhibits wide applications in photocatalysis including photocatalytic water-splitting to produce hydrogen and photo-degradation for organic pollutants because of its outstanding mobility of charge carriers and much higher theoretical specific surface area (Xiang et al, 2012a , b ; Cao et al, 2014 ; Feng J. et al, 2017 ). Many studies have been focused on fabricating GO/semiconductor composites to achieve enhanced visible light photocatalytic activities (Yang et al, 2015 ). For example, Xu et al reported an efficient graphene hybridized with ZnO photocatalyst for the improved UV light photocatalytic activity (Xu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with pristine BiOBr, the peak position of I‐BiOBr slightly shifts to a lower angle, which preliminarily indicates that iodine ion has been successfully doped into BiOBr (Figure 1a,b). [ 29,30 ] All diffraction peaks of g‐C 3 N 4 and I‐BiOBr can be found in the as‐prepared I‐Bi/C 3 N 4 catalyst. More interestingly, the peak intensity of g‐C 3 N 4 becomes stronger when increasing the proportion content of carbon nitride from I‐Bi/C 3 N 4 ‐1 to I‐Bi/C 3 N 4 ‐4 catalyst (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%